A Parabolic-Curvilinear Reverse-Flow Air-Flotation System (PAF) for Removal of Suspended Solids in Sago Starch Production Wastewater Effluents - Oon, Yin Wee; Law, Puong Ling; Kopli, Bujang; Lim, Soh Fong (Research India Publications, 2017)
A Parabolic-Curvilinear Reverse-Flow Air-Flotation Treatment System (PAF) was recently developed for the removal of total suspended solids from sago starch production wastewater effluents. The primary components of the system consist of a parabolic-curved plate, a series of water pumps, an air curtain and valve-froth collection plates to repeat bubbling treatment in a gradually increasing movement flow. Performance tests were carried out by using synthesized sago wastewaters. Performance tests were carried out to determine the total suspended solids and turbidity removal efficiencies. Total suspended solids of the synthesized sago wastewaters ranged from 95 to 515 mg/L, 86.9 to 413 NTU for turbidity and 5.44 to 7.43 for pH. The total suspended solids and turbidity removal efficiencies of this system were found to be proportional to residence time, and inversely proportional to influent flowrate. The highest achievable total suspended solids and turbidity removal efficiencies for this treatment system recorded 85.63% and 77.89%, respectively. The presence of parabolic-curved plate in the system could improve the removal efficiencies as high as 34.22% for total suspended solids and 37.82% for turbidity. The system performance can further be improved by 13.65% for total suspended solids removal and 24.49% for turbidity removal with the installation of air curtain whilst 9.04% for total suspended solids removals and 6.03% for turbidity removals with the installation of water pumps in the system. Additional 17.2% of total suspended solids and 3.1% of turbidity level removals could be achieved by application of chemicals, i.e., alum and sodium aluminate.